(untitled) (Medico Legal Update, 2020)
Background: Diabetic patients were indicated to have an improved risk for cancers of the liver, pancreas, and colon; nevertheless, recently many studies have suggested that diabetes mellitus (DM) decreased possibility for developing the cancer of prostate in men. Objective: To analyze if the levels of prostate-specific antigen (PSA) in serum of men with type two DM were low in comparison with healthy group, and to investigate the factors that could influence the PSA level in diabetic patients. Method: 120 diabetic men patients were analyzed for PSA levels in the serum compared with equal number age-matched control group. The relationships between the serum PSA levels and body mass index (BMI), age, hypertension, smoking and glycosylated hemoglobin (HbA1c) were considered. Results: Serum PSA levels were statistically significantly (p<0.05) lower in diabetic patients compared to healthy men. The present study demonstrated that age, BMI and high HbA1c showed independent determining factors of the PSA level in men. Conclusions: Our study strongly support that DM has inverse relationship with the levels of PSA marker and more severe cases of diabetes mellitus, older age and high body mass index in diabetic patients are associated with lower levels of the serum PSA. This result confirms that diabetes mellitus is a protective factor for prostate cancer among populations.